A mechanistic view of long noncoding RNAs in cancer. (19th October 2021) - Winkler, Lauren; Dimitrova, Nadya
Abstract: Long noncoding RNAs (lncRNAs) have emerged as important modulators of a wide range of biological processes in normal and disease states. In particular, lncRNAs have garnered significant interest as novel players in the molecular pathology of cancer, spurring efforts to define the functions, and elucidate the mechanisms through which cancer‐associated lncRNAs operate. In this review, we discuss the prevalent mechanisms employed by lncRNAs, with a critical assessment of the methodologies used to determine each molecular function. We survey the abilities of cancer‐associated lncRNAs to enact diverse trans functions throughout the nucleus and in the cytoplasm and examine the local roles of cis ‐acting lncRNAs in modulating the expression of neighboring genes. In linking lncRNA functions and mechanisms to their roles in cancer biology, we contend that a detailed molecular understanding of lncRNA functionality is key to elucidating their contributions to tumorigenesis and to unlocking their therapeutic potential. This article is categorized under: Regulatory RNAs/RNAi/Riboswitches > Regulatory RNAs RNA in Disease and Development > RNA in Disease Abstract : Long noncoding RNAs (lncRNAs) are increasingly recognized as functional mediators of cellular processes in both homeostasis and disease. The observation that lncRNAs are frequently dysregulated in cancer has sparked new efforts to understand the functions and mechanisms by which lncRNAs contribute to tumorigenesis.